PENGUATAN PERAN ORANG TUA MELALUI SEMINAR PARENTING BERTEMA PSIKOLOGI BELAJAR DAN PENGASUHAN ANAK DALAM ISLAM - Augusta Rima Salma; Tsalisa Ismi Maryam; Fiki Humaida; Ghaida Zukhruf Tsaniyatsnaini (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The implementation of parenting seminar activities at MI Ma'arif Kumpulrejo 02 with the theme "Psychology of Learning and Child Rearing in Islam" aims to strengthen the role of parents in assisting children's learning process and character development in the digital era. This seminar is motivated by the increasing parenting challenges that are not only related to academics, but also psychological, emotional, and moral aspects of children. This study uses a descriptive qualitative method to describe the process of implementing the seminar, including planning, material delivery, and parental participation. The results showed that this seminar provides a comprehensive understanding of children's learning styles, the importance of effective communication in the family, and the application of Islamic parenting based on the example of Rasulullah SAW. In addition, participants gained insights regarding appropriate parenting styles, the role of parents as school partners, and strategies for assisting children in using gadgets. Six effective parenting techniques which include harmonious emotional relationships, exemplary behavior, acceptance without rejection, strengthening spiritual values, a supportive home environment, and parental self-awareness are proven to be relevant and applicable in family life. Overall, the seminar activities have a positive impact on increasing parental parenting literacy and strengthening cooperation between the school and the family in shaping a generation that is moral, intelligent, and adaptive to the times. ABSTRAK Pelaksanaan kegiatan seminar parenting di MI Ma’arif Kumpulrejo 02 dengan tema "Psikologi Belajar dan Pengasuhan Anak dalam Islam" bertujuan untuk memperkuat peran orang tua dalam mendampingi proses belajar dan perkembangan karakter anak di era digital. Seminar ini dilatarbelakangi oleh meningkatnya tantangan pengasuhan yang tidak hanya berkaitan dengan akademik, tetapi juga aspek psikologis, emosional, dan moral anak. Penelitian ini menggunakan metode kualitatif deskriptif untuk menggambarkan proses pelaksanaan seminar, meliputi perencanaan, penyampaian materi, dan partisipasi orang tua. Hasil penelitian menunjukkan bahwa seminar ini memberikan pemahaman komprehensif mengenai gaya belajar anak, pentingnya komunikasi efektif dalam keluarga, serta penerapan pengasuhan Islami berdasarkan teladan Rasulullah saw. Selain itu, peserta memperoleh wawasan mengenai pola asuh yang tepat, peran orang tua sebagai mitra sekolah, serta strategi pendampingan penggunaan gadget pada anak. Enam teknik pengasuhan efektif yang meliputi hubungan emosional harmonis, keteladanan, penerimaan tanpa penolakan, penguatan nilai spiritual, lingkungan rumah yang mendukung, serta kesadaran diri orang tua terbukti relevan dan dapat diterapkan dalam kehidupan keluarga. Secara keseluruhan, kegiatan seminar memberikan dampak positif terhadap peningkatan literasi pengasuhan orang tua serta memperkuat kerja sama antara sekolah dan keluarga dalam membentuk generasi yang berakhlak, cerdas, dan adaptif terhadap perkembangan zaman.